2016
DOI: 10.33043/jsacp.8.2.49-69
|View full text |Cite
|
Sign up to set email alerts
|

A Social-­‐Justice Informed Evaluation of a Mentorship-Based Program Pairing At-Risk Youth and Holocaust Survivors

Abstract: This paper describes a social justice informed, formative evaluation of a community-based intervention program in our community that paired marginalized Latinx youth and Holocaust survivor mentors. This program is a unique effort to address the issues facing this youth population through difficult dialogues and mentorship from a group who has clearly suffered oppression. Using a qualitative, community-based approach, eight program participants were interviewed to explore the aspects of the program that were he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…When reflecting on learning more about struggles around transitioning and physical and psychological concerns, students often remarked that this information moved them emotionally. Similar to the findings in previous research (Garcia & Frank, 2017;Morgan-Consoli et al, 2016;Vega & McHugh, 2003), 14 of the students used phrases that suggested increased empathy or sympathy. For example, two students wrote that they were now more "sensitive to" or more aware of the military veterans they encounter in their everyday lives and what these military veterans might have experienced or be experiencing.…”
Section: Civilian Students Learn "A Lot" -Trends In Their Reflectionssupporting
confidence: 87%
See 3 more Smart Citations
“…When reflecting on learning more about struggles around transitioning and physical and psychological concerns, students often remarked that this information moved them emotionally. Similar to the findings in previous research (Garcia & Frank, 2017;Morgan-Consoli et al, 2016;Vega & McHugh, 2003), 14 of the students used phrases that suggested increased empathy or sympathy. For example, two students wrote that they were now more "sensitive to" or more aware of the military veterans they encounter in their everyday lives and what these military veterans might have experienced or be experiencing.…”
Section: Civilian Students Learn "A Lot" -Trends In Their Reflectionssupporting
confidence: 87%
“…Vega and McHugh's (2003) students ultimately found that they became emotionally connected to and invested in the people with whom they were working as well as more concerned about senior citizens in general. Similar increases in empathy and openness to new, different populations have been seen in students participating in other service-learning and community-engagement projects (Garcia & Frank, 2017;Morgan-Consoli et al, 2016).…”
Section: The Effects Of Academic-community Engagementmentioning
confidence: 61%
See 2 more Smart Citations